E-041 Toward one-stop stroke management: time variant color overlay for multiphase flat-panel CT angiography. (4th August 2020) - Narsinh, K; Mueller, K; Manhart, M; Hetts, S; Moore, T; Chaney, E; Cooke, D
Abstract : Introduction: Improved functional outcome has been shown in carefully selected patients who are directly transferred to the interventional suite for immediate access to recanalization therapy, bypassing the emergency department (ED) and diagnostic multidetector CT (MDCT). For stroke patients transferred directly to the interventional suite, flat panel CT (FPCT) may provide the necessary diagnostic information regarding intracranial hemorrhage, large vessel patency, clot extent, and collateral supply. However, the large amount of data acquired, typically including 10 phases of contrast-enhancement, can be difficult to review and interpret quickly in the acute stroke setting, and its diagnostic equivalence to MDCT has not been validated. A display format that incorporates all of the multiphasic information into a single time-variant color map may be helpful in facilitating rapid interpretation. Materials and Methods: Between January and October 2019, six acute ischemic stroke patients at a tertiary urban hospital underwent multiphasic FPCT after conventional stroke evaluation with MDCT in the ED. IRB approval was obtained. Data was post-processed on a separate workstation, allowing dynamic visualization of ten 3D volumes in different phases of contrast enhancement, enabling evaluation for hemorrhage, occlusion site, clot extent, and collateral flow. We retrospectively processed these multiphasic scans in a fully automated workflow including rigid motion correction, orbitomeatal line alignment, mask image subtraction, maximum intensity projection (MIP) generation, and production of a single color-coded MIP volume condensing the data contained in the 10 phases of contrast enhancement. Results: Intracranial hemorrhage was not detected in any case, either on MDCT or FPCT. Color-coded MIP images enabled confident diagnosis of large vessel occlusion, clot extent, and collateral flow. The time to acquire FPCT in IR was faster than that to acquire MDCT in the ED (2 vs 17 min). Theoretical time savings averaged 68 min. All patients underwent subsequent mechanical thrombectomy (with TICI 2b/3 results). FPCT perfusion maps were equivalent to MDCT perfusion maps, and accurately predicted core infarct volume on follow-up MRI/CT, as compared by manual segmentation methods. Conclusion: Flat panel CT angiography is a promising tool to enable one-stop shop management of acute ischemic stroke in the interventional suite. Color-coded MIP images enable rapid diagnosis and interpretation of large multiphasic CTA data. Disclosures: K. Narsinh: None. K. Mueller: 5; C; Siemens Healthineers. M. Manhart: 5; C; Siemens Healthineers. S. Hetts: 1; C; Siemens Healthineers, NIH. 2; C; Imperative Medical, MicroVention Terumo, Route 92 Medical. T. Moore: None. E. Chaney: None. D. Cooke: 1; C; Siemens Healthineers.